2008
DOI: 10.1007/s00426-008-0202-2
|View full text |Cite
|
Sign up to set email alerts
|

Microsaccadic modulation of response times in spatial attention tasks

Abstract: Covert shifts of attention are usually reXected in RT diVerences between responses to valid and invalid cues in the Posner spatial attention task. Such inferences about covert shifts of attention do not control for microsaccades in the cue-target interval. We analyzed the eVects of microsaccade orientation on RTs in four conditions, crossing peripheral visual and auditory cues with peripheral visual and auditory discrimination targets. Reaction time was generally faster on trials without microsaccades in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 41 publications
2
19
0
Order By: Relevance
“…By contrast, salient peripheral cues (visual or auditory, informative or uninformative) that engage exogenous attention might result in microsaccade biases opposite to the cue [72,80,83]. The observation of microsaccade biases opposite to salient and abrupt peripheral events is consistent with inhibition of return [16,75,84,85].…”
Section: Attentional and Cognitive Modulation Of Microsaccadesmentioning
confidence: 54%
“…By contrast, salient peripheral cues (visual or auditory, informative or uninformative) that engage exogenous attention might result in microsaccade biases opposite to the cue [72,80,83]. The observation of microsaccade biases opposite to salient and abrupt peripheral events is consistent with inhibition of return [16,75,84,85].…”
Section: Attentional and Cognitive Modulation Of Microsaccadesmentioning
confidence: 54%
“…There is accumulating evidence that the analysis of the timing, rate, and direction of microsaccades provide information about the neural mechanisms underlying vision and certain higher-order cognitive behaviors. For example, microsaccades, which modulate neural activity in visual areas (Martinez-Conde et al, 2000Snodderly et al, 2001;Herrington et al, 2009;Hafed and Krauzlis, 2010;Hass and Horwitz, 2011), have also been shown to be correlated with visual awareness and visuospatial attention (Hafed and Clark, 2002;Engbert and Kliegl, 2003;Laubrock et al, 2005;Betta and Turatto, 2006;Engbert, 2006;Otero-Millan et al, 2008;Cui et al, 2009;Herrington et al, 2009;Kliegl et al, 2009;Pastukhov and Braun, 2010). Given that the temporal dynamics of each eye can differ throughout a given microsaccade, our results suggest that the knowledge of the motion of both eyes could improve the correlation observed between microsaccades and neural activity (or behavior).…”
Section: Binocular Microsaccades and The Implication For Studies Of Vmentioning
confidence: 68%
“…Divided attention increases reaction time (Ninio & Kahneman, 1974), so perhaps when microsaccades are made immediately before the target appears, visual attention is divided between the attentional shifts accompanying the microsaccades and the attention directed to monitoring target onset, resulting in longer manual reaction times. There is evidence that, in normal observers, faster manual reaction times are associated with a reduction in the frequency of microsaccades (Betta & Turatto, 2006; Kliegl, Rolfs, Laubrock, & Engbert, 2009). We speculate that, for the strabismic amblyope, the numerous microsaccades, made while struggling to maintain fixation, result in all types of reactions being delayed by a fluctuating wave of refractoriness and the accompanying shifts in attention.…”
Section: Discussionmentioning
confidence: 99%